Multiple responses optimization in the development of a headspace gas chromatography method for the determination of residual solvents in pharmaceuticals - Carla M. Teglia; Milagros Montemurro; María M. De Zan; María S. Cámara (Elsevier, 2015)
An efficient generic static headspace gas chromatography (HSGC) method was developed, optimized and validated for the routine determination of several residual solvents (RS) in drug substance, using a strategy with two sets of calibration. Dimethylsulfoxide (DMSO) was selected as the sample diluent and internal standards were used to minimize signal variations due to the preparative step. A gas chromatograph from Agilent Model 6890 equipped with flame ionization detector (FID) and a DB-624 (30 m×0.53 mm i.d., 3.00 µm film thickness) column was used. The inlet split ratio was 5:1. The influencing factors in the chromatographic separation of the analytes were determined through a fractional factorial experimental design. Significant variables: the initial temperature (IT), the final temperature (FT) of the oven and the carrier gas flow rate (F) were optimized using a central composite design. Response transformation and desirability function were applied to find out the optimal combination of the chromatographic variables to achieve an adequate resolution of the analytes and short analysis time. These conditions were 30 °C for IT, 158 °C for FT and 1.90 mL/min for F. The method was proven to be accurate, linear in a wide range and very sensitive for the analyzed solvents through a comprehensive validation according to the ICH guidelines. Keywords: Headspace gas chromatography, Residual solvents, Pharmaceuticals, Surface response methodology, Desirability function